Pattern and associated factors of COVID-19 knowledge, attitude and practice (KAP) among COVID-19-comorbid patients: a systematic review and meta-analysis - Rehman, Anees ur; Tasleem, Zermina; Muhammad, Sohail Ayaz; Rasool, Muhammad Fawad; Shah, Shahid; Jabeen, Gul; Arif, Sonia; Omar Babkair, Lujain Salim; Kadumi, Yahya Jaber; Alghamdi, Saleh; Almarzoky Abuhussain, Safa S.; Khayyat, Sarah M.; et al. (Frontiers in Public Health, 2024)
Background The COVID-19 comorbid population is at higher risk of developing severe health issues like acute respiratory distress syndrome, coagulation syndrome, metabolic acidosis, and septic shock, potentially leading to patient death. Patients’ knowledge, attitudes, and practices (KAP) significantly influence their response to the pandemic and aid in enhancing health policy implementation. Objective To identify and evaluate the pattern and associated factors to COVID-19 knowledge, attitude, and practice among individuals with comorbidities. Methodology The systematic review followed the PRISMA guidelines. Relevant studies assessing the KAP of comorbid patients were retrieved by carefully searching the PubMed and Google Scholar databases. The appraisal tool for cross-sectional studies was used to determine the quality of the included studies and the risk of biases. Results Eighteen studies met the inclusion criteria and were included in the review. The pooled sample size of the included studies was 9,104. Different comorbidities reported in the studies include hypertension, diabetes, psychological disorders, and cancer. Pooled analysis showed that 65% of patients showed good knowledge, 57% of patients showed a positive attitude and 51% of patients followed good practices to manage the COVID-19 in presence of their comorbid condition. Significant factors impacting knowledge, attitude and practice in COVID-19 comorbid patients were ethnicity OR 1.78 [95% CI 1.35–2.32]; educational status 3.2 [2.79–3.58]; urban residence 2.43 [1.65–3.02]; employment Status 1.67[1.34–2.12]; financial Status 4.02[3.66–4.38]; occupation 3.65[3.31–4.25]; information Source 2.64[2.19–3.26]; comorbidity 3.28[2.78–3.61]; and duration of chronic illness 1.59[1.31–2.04]. Conclusion Comorbid COVID-19 patients showed good knowledge, positive attitude and good practice towards the management of the disease.